Preventing Foodborne Illness: Cyclosporiasis - Christopher Pabst; Jaysankar De; Renée Goodrich Schneider; Keith R. Schneider (EDIS, 2019)
Cyclosporiasis is an intestinal illness caused by the microscopic parasite Cyclospora cayetanensis. People can become infected with Cyclospora by consuming food or water contaminated with the parasite. People living or traveling in countries where cyclosporiasis is endemic may be at increased risk for infection. This 6-page publication is part of the Preventing Foodborne Illness series and describes symptoms and strategies for cyclosporiasis prevention for farmers, restaurants and retailers, and consumers. This major revision was written by Christopher R. Pabst, Jaysankar De, Renée Goodrich-Schneider, and Keith R. Schneider and published by the UF/IFAS Food Science and Human Nutrition Department. http://edis.ifas.ufl.edu/fs130